2009
DOI: 10.2190/wr.14.1.g
|View full text |Cite
|
Sign up to set email alerts
|

Gender Identity Issues and Workplace Discrimination: The Transgender Experience

Abstract: Mainstream social constructions of gender tend to demand conformity by adhering to only two choices of gender identity, male and female. Transgender individuals transgress this binary conception of gender by deviating from the societal gender norms associated with the sex assigned at birth. Using a combination of face-to-face and phone interviews to collect data, twenty-six interviews were conducted with male-identified transgender individuals aged 18 to 57 from throughout the United States. All participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 18 publications
2
62
0
9
Order By: Relevance
“…Khan and colleagues (2009), for example, found that Bangladeshi transgender persons are likely to have difficult lives from early childhood; they are excluded from society and live their lives as marginalized people, an experience that often adversely affects their health and well-being. Similarly, transgender individuals living in Western countries face various forms of discrimination in many different settings, including workplaces, educational institutions, health care services, religious or church organizations, and social welfare agencies, and also as a consequence of government policies (Budge, Tebbe, & Howard, 2010 Dentice, 2009;Dispenza, Watson, Chung, & Brack, 2012;McKinney, 2005;Sausa et al, 2007;Yarhouse & Carrs, 2012). Furthermore, in part as a result of their marginalization from other work environments, transgender individuals tend to engage in sex work, and therefore have a higher risk of HIV infection (Bockting, Robinson, & Rosser, 1998;Khan et al, 2009;Melendez & Pinto, 2007;Nemoto, Sausa, Operario, & Keatley, 2006;Sausa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Khan and colleagues (2009), for example, found that Bangladeshi transgender persons are likely to have difficult lives from early childhood; they are excluded from society and live their lives as marginalized people, an experience that often adversely affects their health and well-being. Similarly, transgender individuals living in Western countries face various forms of discrimination in many different settings, including workplaces, educational institutions, health care services, religious or church organizations, and social welfare agencies, and also as a consequence of government policies (Budge, Tebbe, & Howard, 2010 Dentice, 2009;Dispenza, Watson, Chung, & Brack, 2012;McKinney, 2005;Sausa et al, 2007;Yarhouse & Carrs, 2012). Furthermore, in part as a result of their marginalization from other work environments, transgender individuals tend to engage in sex work, and therefore have a higher risk of HIV infection (Bockting, Robinson, & Rosser, 1998;Khan et al, 2009;Melendez & Pinto, 2007;Nemoto, Sausa, Operario, & Keatley, 2006;Sausa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Klöppel, 2010 (vgl. Alexander & Yescavage, 2003;de Silva, 2005;Dietert & Dentice, 2009;Lindemann, 2011).…”
Section: "Sexuelle Orientierung" Lsbt Heterosexualität Und Queerunclassified
“…zur Kündigung (vgl. Brown & Rounsley, 1996;Dietert & Dentice, 2009). Als erstes Mittel, das Thema Transidentität organisational aufzugreifen, schlagen Barclay und Scott (2006) vor, eine klare Unternehmensrichtlinie zum Vorgehen im Falle einer Geschlechtsanpassung zu formulieren.…”
Section: Forschung Zu Den Phänomenen Transidentität Und Bisexualitätunclassified
See 1 more Smart Citation
“…lesbian, gay male, bisexual, and transsexual employees, and (if adding an I) intersex employees . However, transsexuality and intersexuality are not directly linked to sexuality or sexual preferences (Dietert and Dentice 2009), and heterosexuality is usually excluded in organizational diversity practices, although policies protecting employees on the basis of sexual orientation protect heterosexual employees as well. Whatever the terms and definitions used in this dimension(s) of diversity, by far the most frequently addressed groups in diversity research and practice are gay and lesbian employees, a focus that this paper also has.…”
mentioning
confidence: 99%